1998
DOI: 10.1038/bjc.1998.246
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of urokinase plasminogen activator in primary breast carcinoma: comparison of two immunoassay methods

Abstract: Summary Urokinase-type plasminogen activator (uPA) is a potentially important prognostic factor in breast cancer for identifying patients at high risk of recurrence. This retrospective study assessed two enzyme-linked immunosorbent assay (ELISA) methods measuring uPA antigen levels in 499 primary breast cancer cytosols. Both uPA methods were applied to cytosols used routinely for oestrogen (ER) and progesterone (PgR) receptor assays. uPA was determined using a classical ELISA method (Imubind; American Diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…We confirm the negative correlation between uPA levels and ER status, and the positive correlations between uPA levels, histological grade and tumour size (Duffy, 1996). In our study, the prognostic value of uPA was comparable to that of lymph node involvement, and a high uPA level was still an independent prognostic indicator in multivariate analysis, confirming previous studies based on ELISA methods (Foekens et al, 1992;Jänicke et al, 1993;Duffy, 1996;Bouchet et al, 1998) or LIA (Fernö et al, 1996;Bouchet et al, 1998;Peyrat et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We confirm the negative correlation between uPA levels and ER status, and the positive correlations between uPA levels, histological grade and tumour size (Duffy, 1996). In our study, the prognostic value of uPA was comparable to that of lymph node involvement, and a high uPA level was still an independent prognostic indicator in multivariate analysis, confirming previous studies based on ELISA methods (Foekens et al, 1992;Jänicke et al, 1993;Duffy, 1996;Bouchet et al, 1998) or LIA (Fernö et al, 1996;Bouchet et al, 1998;Peyrat et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…In this study we used hormone receptor buffer, which yields lower uPA values than Triton X-100 buffer (Janicke et al, 1994a;Knoop et al, 1998). However, significant prognostic value has also been observed with cytosols prepared for hormone receptor assays (Foekens et al, 1992;Bouchet et al, 1994Bouchet et al, , 1998Jänicke et al, 1994a;Fernö et al, 1996;Peyrat et al, 1998). Our technique has the advantage of being automated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The over-expression of uPA has been detected in various malignancies including breast (Miyake et al, 1999), prostate (Yang et al, 2000), colon (Duggan et al, 1995), and pancreatic (Lee et al, 2003b). Some data have shown that a high level of uPA in tumors is associated with a rapid disease progression and a poor prognosis (Solomayer et al, 1997;Bouchetm et al, 1998). In addition, studies performed with both in vitro and in vivo experimental models have demonstrates that the levels of uPA are closely associated with the degree of tumor cell invasion (Xing et al, 1996).…”
Section: Introductionmentioning
confidence: 99%